Relations between vertical and horizontal movements of the Earth crust - Zakarevičius, Algimantas (Geodesy and Cartography, 2012)
Horizontal and vertical movements of the Earth crust are interrelated, because the same forces affecting the Earth crust cause them. There is a both-side interrelation between deformations of the Earth crust and spreading of tectonic tensions. So, it is possible to assess the indicators of horizontal deformations and to establish the regularities of their changes by examining the measured values of vertical deformations of the Earth crust, and vice versa. The established analytical interrelation between horizontal and vertical deformations of the Earth crust is described in the paper. The interrelation has been found by application the vector and tensor analysis. An algorithm for assessing the indicators of horizontal deformations of the Earth crust according to the results of measuring the vertical movements is provided. The method of finite elements is applied for assessment the indicators of deformations. A numerical example of application of the developed algorithm is provided as well.Article in Lithuanian.Vertikaliųjų ir horizontaliųjų Žemės plutos judesių sąsajosSantrauka. Horizontalieji ir vertikalieji Žemės plutos judesiai tarpusavyje susiję, nes jie yra tų pačių Žemės plutą veikiančių jėgų pasekmė. Taip pat yra abipusis ryšys tarp Žemės plutos deformacijų ir tektoninių įtampų sklaidos. Todėl pagal išmatuotas vertikaliųjų Žemės plutos deformacijų reikšmes galima įvertinti horizontaliųjų deformacijų rodiklius, nustatyti jų kaitos dėsningumus ir atvirkščiai. Straipsnyje pateikta nustatytoji analitinė sąsaja tarp horizontaliųjų bei vertikaliųjų Žemės plutos deformacijų. Sąsajoms nustatyti taikyta vektorinė bei tenzorinė analizė. Pateiktas algoritmas horizontaliųjų Žemės plutos deformacijų rodikliams įvertinti pagal vertikaliųjų judesių matavimo rezultatus. Deformacijų rodikliai įvertinti baigtinių elementų metodu. Pateiktas parengto algoritmo taikymo skaitinis pavyzdys.Prasminiai žodžiai: Žemės plutos judesiai, tektoninės įtampos, deformacijų tenzorius, svarbiausios deformacijos.First published online: 03 Aug 2012